The Influence of Korean Dramas on Romantic Communication Patterns of Indonesian Teenagers - Saputra, Moch Panji Agung; Kalfin; Laksito, Grida Saktian (International Journal of Linguistics, Communication, and Broadcasting, 2025)
The phenomenon of the Hallyu Wave, particularly through Korean dramas (K-dramas), has become a significant global cultural current that shapes teenagers' lifestyles and communication patterns. In Indonesia, K-dramas are not only consumed as entertainment but also function as cultural references in constructing interpersonal relationships, especially in the romantic domain. This study aims to analyze the influence of K-dramas on the romantic communication patterns of Indonesian adolescents, focusing on the forms of communication adopted and the negotiation process with local cultural values. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation with adolescents aged 15–19 years in Bandung who actively consume K-dramas. The data were analyzed using Miles & Huberman's interactive analysis model, which includes stages of data reduction, data presentation, and conclusion drawing. The findings reveal three main forms of romantic communication influenced by K-dramas: (1) verbal communication, reflected in the adoption of terms of endearment such as oppa, yeobo, “sayang,” and “beb,” which illustrates linguistic hybridity; (2) nonverbal communication, such as holding hands, hugs, and meaningful gazes, although adapted to Indonesian norms of politeness and social boundaries; and (3) digital expressions, including emoticons, stickers, and K-drama quotes, which function both as symbols of affection and as markers of engagement with global popular culture. This study also finds a process of cultural negotiation in which adolescents selectively adapt Korean romantic communication styles to fit Indonesian collectivist values. The impact is twofold: positively, it enriches emotional vocabulary, fosters sensitivity, and promotes cross-cultural openness; Negatively, it risks creating unrealistic expectations and undermining local cultural expressions. In conclusion, Indonesian adolescents' romantic communication patterns represent a hybrid form resulting from the dynamic interaction between global influences and local values. Adolescents are not passive consumers but active agents who internalize, adapt, and negotiate popular culture in shaping their interpersonal communication practices.